Access and benefit sharing policies for climate resilient seed systems: matching global commitments with national realities. - Halewood, Michael; Otieno, G.; Nkhoma, C.; Kasasa, P.; Mulumba, John W.; Gapusi, J.; Jonge, B. de (ISSD, 2016)
This synthesis paper provides a summary of main findings on climate resilient seed systems and access and benefit sharing of case studies from Uganda, Rwanda, Zambia and Zimbabwe. This study analyses what is actually happening at the national and subnational levels in terms of climate change, its impacts on particular crops, what experiences countries have had to date in terms of accessing, using and sharing benefits derived from genetic resources for climate change adaptation, and what kinds of ABS policy initiatives or reforms could help those countries to make better use of genetic diversity for climate change adaptation in the future. This study is designed to analyze how these different ‘threads’ come together at national and subnational level in the four countries.